2017
DOI: 10.1080/14647273.2017.1283446
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Probiotic supplementation and the effects on weight loss, glycaemia and lipid profiles in women with polycystic ovary syndrome: a randomized, double-blind, placebo-controlled trial

Abstract: The aim of the current study was to assess the effects of probiotic supplementation on weight loss, glycaemia and lipid profiles in women with polycystic ovary syndrome (PCOS). In a randomized, double-blind, placebo-controlled trial, 60 women with PCOS were randomized to receive probiotic capsule (n = 30) or placebo (n = 30) for 12 weeks. Consumption of probiotic supplements resulted in a significant reduction in weight (-0.5 ± 0.4 vs. +0.1 ± 1.0 kg, p = 0.004) and BMI (-0.2 ± 0.2 vs. +0.03 ± 0.4 kg/m, p = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 32 publications
2
62
1
9
Order By: Relevance
“…Previous studies have shown several beneficial effects of probiotic supplementation on glycemic control in PCOS patients [ 9 , 10 ]. Moreover, some researchers have demonstrated that probiotic consumption in patients with osteoarthritis [ 11 ], type 2 diabetes mellitus (T2DM) [ 12 ], and gestational diabetes mellitus (GDM) [ 13 ] was associated with decreased inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown several beneficial effects of probiotic supplementation on glycemic control in PCOS patients [ 9 , 10 ]. Moreover, some researchers have demonstrated that probiotic consumption in patients with osteoarthritis [ 11 ], type 2 diabetes mellitus (T2DM) [ 12 ], and gestational diabetes mellitus (GDM) [ 13 ] was associated with decreased inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, dry and freeze probiotics of Lactobacillus acidophilus, Lactobacillus casei and Bifidobacterium bifidum were used. Compared to the present study, a more limited range of probiotics was used and prebiotic was not used [14]. Furthermore, a 2019 meta-analysis (N = 8 trials, nine treatment arms), reported beneficial effects of pro−/synbiotics supplementation on insulin resistance indices without any significant effects on anthropometric measurements [22].…”
Section: Discussionmentioning
confidence: 72%
“…Diet and dietary factors can be very effective in modifying the disease. Probiotics and prebiotics dietary are considerations [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A study done in Iran by Ahmadi et al in PCOS women reported that Probiotic supplementation containing Lactobacillus Acidophilus, Lactobacillus Casei and Bifidobacterium Bifidum species for 12 weeks had promising effects not only on weight loss and markers of insulin resistance but also on triglycerides and VLDL-C [25]. Rajkumar et al (2015) found that Probiotic supplementation among hale and hearty young individuals for 6 weeks resulted in a significant reduction in total-cholesterol, LDL-C, triglycerides and a significant increase in HDL-cholesterol concentrations [26].…”
Section: Discussionmentioning
confidence: 99%